Pajak Terhadap Mata Uang Virtual Di Indonesia - Resky Iskandar, Adita Ayu; Razak, Abdul; Naswar, Naswar (Widya Yuridika, 2023)
This study aims to analyze the legality of applying taxes to cryptocurrency In Indonesia and to analyze the mechanism of tax collection against cryptocurrency In Indonesia. This type of research is normative research that discusses the legality of applying taxes to cryptocurrency In Indonesia, by examining library materials or secondary data consisting of primary legal materials, even secondary law and tertiary legal materials.The results of the research show that: 1) The legality of applying taxes to cryptocurrency In Indonesia is Minister of Finance Regulation (PMK) Number 68/PMK.03/2022 concerning Income Tax and Value Added Tax on Crypto Asset Transactions. This crypto tax rule applies starting May 1, 2022, for all types of crypto asset transactions such as trading crypto assets for fiat currency, swapping crypto assets for other crypto, or exchanging crypto assets for goods. other than crypto assets and/or services. 2) Mechanism of tax collection against cryptocurrency In Indonesia is that the Government appoints a third party as a collector of VAT on trading crypto assets and Income Tax Article 22 on crypto asset transactions. The intended VAT and crypto PPh collectors are Trade Operators Through Electronic Systems (PPMSE) who are taxpayers who have been confirmed as Taxable Entrepreneurs (PKP), both domestically and abroad.